2021
DOI: 10.1101/2021.07.09.451781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TNF-mediated neuroinflammation is linked to neuronal necroptosis in Alzheimer’s disease hippocampus

Abstract: The pathogenetic mechanisms underlying neuronal death and dysfunction in Alzheimer’s disease (AD) remain unclear. However, chronic neuroinflammation has been implicated in stimulating or exacerbating neuronal damage. The tumor necrosis factor (TNF) superfamily of cytokines are involved in many systemic chronic inflammatory and degenerative conditions and are amongst the key mediators of neuroinflammation. TNF binds to the TNFR1 and TNFR2 receptors to activate diverse cellular responses that can be either neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…Conversely, we found enrichment of Necroptosis-related pathways in the post-COVID humanized microbiota vehicle mice that were reduced in post-COVID humanized microbiota probiotic-treated mice. This result might be associated with the effect of the probiotic counteracting the increase in TNF-α expression since this cytokine triggers this kind of neuronal cell death [100,101]. Accordingly, with these data, we also observed a neuroprotective effect of B. longum that prevented memory impairment induced in a murine model of coronavirus lung infection.…”
Section: Discussionsupporting
confidence: 74%
“…Conversely, we found enrichment of Necroptosis-related pathways in the post-COVID humanized microbiota vehicle mice that were reduced in post-COVID humanized microbiota probiotic-treated mice. This result might be associated with the effect of the probiotic counteracting the increase in TNF-α expression since this cytokine triggers this kind of neuronal cell death [100,101]. Accordingly, with these data, we also observed a neuroprotective effect of B. longum that prevented memory impairment induced in a murine model of coronavirus lung infection.…”
Section: Discussionsupporting
confidence: 74%
“…This suggests that necrosome can be activated within neurons, directly causing neuronal death ( 308 ). Building on these findings, another study demonstrated co-localization of these proteins within the same neurons upon their exposure to TNFα and co-immunoprecipitation of pRIP3 and MLKL, which additionally strengthens the argument of these proteins interacting to form necrosome within neurons ( 309 ).…”
Section: Smocs Inducing Cell Deathmentioning
confidence: 56%
“…Necroptosis is closely associated with the pathogenesis of various neurodegenerative diseases ( 279 , 306 ), such as AD ( 307 309 ), PD ( 310 , 311 ), ALS ( 312 , 313 ), and multiple sclerosis ( 314 , 315 ). Recently, a direct link has been established between necrosome and neuronal loss in the brains of clinical and preclinical patients with AD.…”
Section: Smocs Inducing Cell Deathmentioning
confidence: 99%
“…In addition to being a potent inflammatory cytokine, TNF-alpha is a powerful modulator of glutamate uptake, with TNF-alpha application to cultured astrocytes significantly reducing glutamate uptake (Ye and Sontheimer, 1996), at least in part through a downregulation of glutamate transporters (Zou and Crews, 2005). Importantly, TNF-alpha elevations are readily observed in the AD hippocampus (Jayaraman et al, 2021; Naghibi et al, 2021; Zhao et al, 2003). Therefore, it is possible that GLT-1 deficits promote the overactivation of astrocytic NMDARs, driving the release of TNF-alpha.…”
Section: Discussionmentioning
confidence: 99%